Carbonylation of cyclohexene with carbon dioxide (CO2) using transition metals as heterogeneous and homogeneous catalysts - Sekaleli, Bafokeng Thabelo (Rhodes University, Faculty of Science, Department of Chemistry)
From a green chemistry perspective, carbon dioxide (CO2) emerges as an appealing C1 synthon, given its abundance in the atmosphere and cost-effectiveness. Many essential chemicals for daily life are derived from fossilized carbon sources like coal, petroleum, and natural gas. However, the by-product of these processes, CO2, poses environmental risks when excessively emitted as a greenhouse gas. Achieving a balance between carbon emissions and removal is crucial to address environmental concerns surrounding CO2. Utilizing CO2 as a C1 source in organic synthesis holds promise for mitigating this balance in the long term. Combining CO2 with other underutilized fine chemicals, such as alkanes, alkenes, and alkynes, to produce more valuable platform chemicals presents an economically viable strategy due to carbon dioxide's abundance, low cost, and recyclability. Despite its simplicity, CO2's high thermodynamic stability and low kinetic reactivity, owing to its highly oxidized state, pose challenges to its use as a feedstock. Overcoming these hurdles requires catalysts to enhance CO2 reactivity. Our work focuses on developing and employing catalytic systems capable of activating CO2 as a C1 synthon in reactions with cyclohexene and a reducing agent to yield carboxylic acids or esters. In one approach, we have developed heterogeneous catalyst systems comprising transition metals (Au, Fe, Ni, Ru) supported on metal oxide (TiO2). Characterization techniques such as TEM, EDX, UV-Vis, BET, and XRD were used to study the properties of these materials. The catalysts were evaluated in a reaction involving cyclohexene, CO2, and H2O. In another approach, we explored the use of cyclo-tris(tetracarbonylruthenium) [Ru3(CO)12] as a homogeneous catalyst in a reaction involving cyclohexene, methanol, and CO2 in the presence of an ionic liquid, 1-Butyl-3-methylimidazolium chloride ([BMIM]+Cl-). 1H NMR and ATR-FT-IR were utilized to characterize [BMIM]+Cl-. The reaction product was characterised utilizing GC-MS. Upon seeing that Ru3(CO)12 changes color from orange to black when exposed to heat, an investigation was undertaken on the kind of transformations that the catalyst undergoes. This investigation was carried out with the hopes of finding the structures that could be resulting from Ru3(CO)12 during the reaction and their significance to it. The orange and black Ru complexes were characterized utilizing DSC, TGA, ATR-FT-IR and PXRD.
Keywords: Carbonylation; Carbon dioxide; Catalysts; Transition metals; Cyclohexene